2014
DOI: 10.5194/npg-21-127-2014
|View full text |Cite
|
Sign up to set email alerts
|

The comparative study of chaoticity and dynamical complexity of the low-latitude ionosphere, over Nigeria, during quiet and disturbed days

Abstract: Abstract. The deterministic chaotic behavior and dynamical complexity of the space plasma dynamical system over Nigeria are analyzed in this study and characterized. The study was carried out using GPS (Global Positioning System) TEC (Total Electron Content) time series, measured in the year 2011 at three GPS receiver stations within Nigeria, which lies within the equatorial ionization anomaly region. The TEC time series for the five quietest and five most disturbed days of each month of the year were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 38 publications
4
29
1
Order By: Relevance
“…Coraddu et al (2005) showed the Tsallis entropy generalization for Lyapunov exponents. Further details can be found in Ogunsua et al (2014); they were able to investigate the similarities in their response to the complex dynamics of the ionosphere, and this informs the further use of the two quantities as indices to study the day-to-day variation of ionospheric behaviour in this work.…”
Section: Computation Of Tsallis Entropy and Principles Of Non-extensimentioning
confidence: 99%
See 4 more Smart Citations
“…Coraddu et al (2005) showed the Tsallis entropy generalization for Lyapunov exponents. Further details can be found in Ogunsua et al (2014); they were able to investigate the similarities in their response to the complex dynamics of the ionosphere, and this informs the further use of the two quantities as indices to study the day-to-day variation of ionospheric behaviour in this work.…”
Section: Computation Of Tsallis Entropy and Principles Of Non-extensimentioning
confidence: 99%
“…A similar approach to the computation of the correlation dimension was used by Unnikrishnan and Ravindran (2010) to determine the correlation dimension of detrended TEC data for some stations in India, which lies within the equatorial region, like Nigeria. Ogunsua et al (2014) also used similar methods for some detrended TEC from Nigerian stations.…”
Section: Correlation Dimensionmentioning
confidence: 99%
See 3 more Smart Citations